Analisis Materi Struktur Atom Pada Buku Teks Kimia Kelas X SMA/MA - Syahra Ayu Pratiwi; Abdul Hadjranul Fatah; Syarpin Syarpin (FKIP Universitas Palangka Raya, 2020)
This research is a qualitative research. This research method is a descriptive research method. The research instrument used was the concept label identification table and the type of representation, the concept label conformity identification table with the syllabus, the discourse macro structure model, and the chemical representation criteria table. The results showed that the concept labels contained in book A were 27 concept labels and had 50 types of representations divided into macroscopic, submicroscopic, symbolic typologies. The concept labels contained in book B are 32 concept labels with 68 types of representations divided into macroscopic, submicroscopic, and symbolic typologies. The suitability of the concept textbook labels A and text book B to the 2013 curriculum curriculum chemistry there are 31 concept labels that correspond to the K-13 chemical syllabus. Book A's macro structure reaches level 7 of the elaboration dimension, and book B reaches level 7 of the elaboration dimension. The chemical representation criteria for the concept of atomic structure in book A have 21 representations, and in book B there are 26 representations.